Low-temperature welded PAN/TPU composite nanofiber membranes for water filtration. (June 2022) - Chen, Yang; Wang, Ning; Jensen, Martin; Li, Xianfeng
Abstract: Nanofiber membranes have attracted considerable interest in water filtration owing to their unique structure and excellent performance, but large pore size and wide pore size distribution combined with weak inter-fiber strength are major limitations for practical applications. This work describes a facile and efficient method for nanofiber membrane fabrication with stable mechanical properties, high separation and excellent antifouling performance. The nanofiber membranes are prepared from a mixture of a low melting point polymer (thermoplastic polyurethane, TPU, T m = 52 °C) and a structural skeleton-forming polymer (polyacrylonitrile, PAN, T m = 317 °C) that undergoes electrospinning and hot-pressing. Hot-pressing treatment at 50–80 °C and 2 MPa melts the TPU phase to create inter-fiber connections, thereby reducing the nanofiber membrane pore size and improving its dimensional stability and mechanical properties. The connectivity of the nanofiber membrane can be controlled by adjusting the ratio of TPU and PAN in the nanofiber and the hot-pressing temperature. The tensile strength and Young's modulus of the hot-pressed membrane are 24.5 MPa and 630.6 MPa, which are 4.8 times and 6.0 times higher than the nascent membrane, respectively. The membrane pressed at 80 °C shows excellent filtration performance, with a high pure water flux of 8490 L m −2 h −1 and active sludge and 100 nm SiO2 suspension retention efficiency of 99.99%. In addition, the hot-pressed membranes exhibited excellent antifouling performance and mechanical properties, meet the reusability and long-term service demand. Therefore, hot-pressed composite nanofiber membranes made of low melting point thermoplastic polymer and a skeleton polymer provide a facile and economical approach for the development of high-performance separation media. Graphical abstract: Unlabelled Image Highlights: A chemical free, mild hot-pressing strategy to prepare PAN/TPU composite nanofiber separation membrane. Improved the mechanical properties and pore size structure of electrospun membranes. Highly efficient removal of 100 nm SiO2 particles and active sludge suspensions under high flux. The nanofiber membranes exhibit high performance as filtration media. The structure and properties of nanofiber membranes can be tailored by the PAN/TPU ratio and the hot-pressing temperature.